1979
DOI: 10.1136/bmj.2.6187.414
|View full text |Cite
|
Sign up to set email alerts
|

Referral of mothers and infants for intensive care.

Abstract: Summary and conclusions During 1975-7, 96

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…These included the obstetric factors present before delivery and extra information on ventilation and other complications after birth (table IV). We too had thought that antenatal transfer of our patients had improved their outcome; certainly the crude mortalities for the 10) 9 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) 7 (3)(4)(5)(6)(7)(8)(9) inborn, outborn, and in utero transfer groups suggested that infants transferred after birth had a higher mortality. Closer examination of 1-70) 07(02-10) 09(02-10) our study populations, however, showed that the outborn babies )-7-5) 7-2(6-7-7-4) 7-2(6-6-7-3) suypp were more immature and had a lower birth weight, and when these factors were taken into account there was no difference in the study populations.…”
mentioning
confidence: 94%
“…These included the obstetric factors present before delivery and extra information on ventilation and other complications after birth (table IV). We too had thought that antenatal transfer of our patients had improved their outcome; certainly the crude mortalities for the 10) 9 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) 7 (3)(4)(5)(6)(7)(8)(9) inborn, outborn, and in utero transfer groups suggested that infants transferred after birth had a higher mortality. Closer examination of 1-70) 07(02-10) 09(02-10) our study populations, however, showed that the outborn babies )-7-5) 7-2(6-7-7-4) 7-2(6-6-7-3) suypp were more immature and had a lower birth weight, and when these factors were taken into account there was no difference in the study populations.…”
mentioning
confidence: 94%
“…There is evidence to support antenatal transfer to a regional perinatal centre as a manoeuvre to improve neonatal survival (Lobb et al 1983;Blake et al 1979). However, increasing numbers of antenatal transfers present at least two problems.…”
Section: Discussionmentioning
confidence: 99%
“…One is to increase staffing and facilities at a district level. Thus, if the approach to improving current practices in resuscitation and early stabilization at district hospitals is to be by There is evidence to support antenatal transfer to a regional perinatal centre as a manoeuvre to improve neonatal survival (Lobb et al 1983;Blake et al 1979). Wood et al (1984) have recently argued that 'better provision and training of district staff in immediate care at birth would probably be of more benefit in Wessex than the setting u p of a regional neonatal unit specialising in advanced neonatal intensive care.'…”
Section: Discussionmentioning
confidence: 99%